Determination of 2-methylimidazole and 4-methylimidazole in caramel colors by capillary electrophoresis - Petruci, João Flávio Da Silveira [UNESP]; Pereira, Elisabete Alves; Cardoso, Arnaldo Alves [UNESP] (American Chemical Society (ACS), 2013)
The use of chemical preservative compounds is common in the food products industry. Caramel color is the most usual additive used in beverages, desserts, and breads worldwide. During its fabrication process, 2- and 4-methylimidazole (MeI), highly carcinogenic compounds, are generated. In these cases, the development of reliable analytical methods for the monitoring of undesirable compounds is necessary. The primary procedure for the analysis of 2- and 4-MeI is using LC- or GC-MS techniques. These procedures are time-consuming and require large amounts of organic solvents and several pretreatment steps. This prevents the routine use of this procedure. This paper describes a rapid, efficient, and simple method using capillary electrophoresis (CE) for the separation and determination of 2- and 4-MeI in caramel colors. The analyses were performed using a 75 μm i.d. uncoated fused-silica capillary with an effective length of 40 cm and a running electrolyte consisting of 160 mmol L-1 phosphate plus 30% acetonitrile. The pH was adjusted to 2.5 with triethylamine. The analytes were separated within 6 min at a voltage of 20 kV. Method validation revealed good repeatability of both migration time (<0.8% RSD) and peak area (<2% RSD). Analytical curves for 2- and 4-MeI were linear in the 0.4-40 mg L-1 concentration interval. Detection limits were 0.16 mg L-1 for 4-MeI and 0.22 mg L-1 for 2-MeI. The extraction recoveries were satisfactory. The developed method showed many advantages when compared to the previously used method. © 2013 American Chemical Society.
Keywords: capillary electrophoresis; caramel color; imidazole; Analytical curves; Carcinogenic compounds; Chemical preservatives; Extraction recovery; Fabrication process; Fused-silica capillaries; Method validations; Capillary electrophoresis; Chemical compounds; Food products; Fused silica; Organic solvents; Separation; Color